Rethinking School-to-Work Transitions in Australia Young People Have Something to Say - Down, Barry (Critical Studies of Education ;, 2018)
This book draws on the stories of thirty-two young Australians to identify the barriers and obstacles they face in 'getting a job' in precarious times and from their vantage point. It maps the kinds of educational policies and practices that need to be created and more widely sustained to assist their career aspirations and life chances. It is timely in terms of contributing to an alternative set of possibilities based on a commitment to the principles and values of social justice, respect, trust, care, democracy and citizenship. In constructing an alternative vision and practice for education and training it advocates the right of all young people to have a say in these broader public debates. In pursuing this agenda, it deliberately sets out to listen to what young people themselves have to say with a view to interrupting the way things are. In other words, the book seeks to identify and explain the dreams, desires and aspirations of young people with a view to creating a new imaginary and socially just future. Rethinking school-to-work transitions: young people have something to say is a wonderful book! It asks those kinds of difficult questions that are necessary for addressing the troubling school-work transitions many young people from marginalised backgrounds face. In particular consideration is given to whether schools continue to be 'savage sorting machines' or whether they can be rethought in ways that support young people from such backgrounds in socially just ways. To engage in such a rethinking Barry Down, John Smyth and Janean Robinson do what might seem obvious - but is rarely done, and rarely done so well - they consult with young people. The young people in this book provide significant evidence of the ways in which many young people are being failed by society - through unfriendly schooling experiences and a precarious employment market. However, at the same time the book captures the hope that many of those interviewed maintain for their futures. These stories are accompanied by insightful theorising which moves beyond critique (as important as that is) to advocating for hopeful possibilities via realistic utopian thinking. In so doing there is a rejection of deficit thinking about young people and their backgrounds, a sophisticated analysis of class, and a reconceptualisation of schooling. This book is important for those who care about social justice, young people, their futures, and education. In the book, seventeen-year-old Janine indicates that she wants to make the world a better place, through the way in which the authors of this book have brought together her and other young people's stories she has already contributed to this ambition. Professor Martin Mills Head of School, University of Queensland, Australia Barry Down, John Smyth and Janean Robinson have set out to understand and advance our thinking related to school-to-work transitions, using a critical theoretical and critical ethnographic framework. In an original design and approach, they analyze the lived experiences of young people who are directly involved, and, importantly, have been directly impacted by the nefarious politico-economic conditions that we now face. This book makes an important contribution to the field, and provides insight and proposals for policymakers, educators and students that should be of great interest to all those concerned with democracy and social justice. Paul R. Carr Professor & Chair-holder UNESCO Chair in Democracy, Global Citizenship and Transformative Education (DCMÉT) Université du Québec en Outaouais (UQO), Gatineau, Québec, Canada.